Artificial rearing alters intestinal microbiota and induces inflammatory response in piglets - Han, Qi; Zhang, Xiaohong; Nian, Haoyang; Liu, Honggui; Li, Xiang; Zhang, Runxiang; Bao, Jun (Frontiers in Microbiology, 2022)
With the ongoing genetic selection for high prolificacy in sow lines and the improvements in environment and farm management, litter size has increased in recent years. Artificial rearing is becoming widely used to raise the surplus piglets in pig industry. This study aimed to investigate the changes that happened in the morphology, microbiota, mucosal barrier function, and transcriptome caused by artificial rearing in piglet colon. Two hundred and forty newborn piglets were randomly assigned into three treatments, sow rearing until weaning (CON group), artificial rearing from day 21 (AR21 group), and artificial rearing from day 7 (AR7 group). On day 35, the piglets were euthanized to collect colon samples. The results showed that the artificially reared-piglets displayed increased pre-weaning diarrhea incidence and reduced growth performance. Artificial rearing changed the diversity and structure of colonic microbiota and increased relative abundance of harmful bacteria, such as Escherichia-Shigella. In addition, the morphological disruption was observed in AR7 group, which was coincided with decreased tight junction proteins and goblet cell numbers. Moreover, the expression of TNFSF11, TNF-α, IL-1β, TLR2, TLR4, MyD88, NF-κB, COX-2, PTGEs, iNOS, IL-2, IL-6, IL-17A, and IFN-γ was upregulated in the colon of the artificially reared-piglets, while the expression of IL-1Ra and IκBα was downregulated, indicating that artificial rearing induced inflammatory response through the activation of NF-κB pathway. Furthermore, artificial rearing regulated SLC family members, which affected solute transport and destroyed intestinal homeostasis. In conclusion, artificial rearing caused microbiota alteration, morphology disruption, the destruction of mucosal barrier function, and inflammatory response, and thus, led to subsequent increased diarrhea incidence and reduced growth performance.